(3GdeMGSHI GdJMdjdjI (B: s (3OQhS h JeGQjf (B/ s - (3MGHj,CMeOs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2020)
(3YehejGJ Mhd GdeMGSHI GdJMdjdjI , eMGSHI GdehGO(B((3WQb Jbjje GdeNRhf(B)(3,WQjbI GdJcGdja GdcdjI (B((3GdGbSGe GdeJLGfSI(B)(3,GdMGdGJ GdNGUI aj MSGH JcdaI GdGfJGL , WQjbI GdJcGdja GdeJZjQI ,WQjbI GdJMejd GdYbdGfj ddJcGdja(B.s
(3eQGLY U(B.123s
Keywords: (3GdeMGSHIs; (3GdeMGSHI GdJMdjdjIs